Longitudinal Analysis of Early Mathematics Learning. Issue 3 (15th February 2018) - Camilli, Gregory; Kim, Sunhee
Abstract: The trend in mathematics achievement from preschool to kindergarten is studied with a longitudinal growth item response theory model. The three measurement occasions included the spring of preschool and the spring and fall of kindergarten. The growth trend was nonlinear, with a steep drop between spring of preschool and fall of kindergarten. The modeling results provide validation for the argument that a classroom assessment in mathematics can be used to assess developmental skill levels that are consistent with a theory of early mathematics acquisition. The statistical model employed enables an effective illustration of overall gains and individual variability. Implications of the summer loss are discussed as well as model limitations.